Kajian Psikologi Humanistik Abraham Maslow terhadap Tokoh Utama dalam Novel Senja Hujan Cerita yang Telah Usai Karya Boy Candra - Sihombing, Sholeh; Gissela Dameria B. Sinulingga; Renta Giofani; Seskya Damayanti (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study employs a psychological approach to literature to examine the main character in Boy Candra’s novel Senja, Hujan, dan Cerita yang Telah Usai. The objective is to analyze the character’s psychological dynamics through Abraham Maslow’s hierarchy of needs, encompassing physiological needs, safety, love and belonging, esteem, and self-actualization. This research adopts a qualitative descriptive method, with data in the form of words, phrases, and sentences extracted from the novel and interpreted based on Maslow’s theoretical framework. The findings indicate that the main character experiences a progressive psychological development. The fulfillment of physiological and safety needs is reflected in efforts to maintain stability and emotional security. The need for love and belonging emerges through the character’s longing for meaningful relationships, while esteem needs are shown in attempts to preserve self-worth despite emotional setbacks. Ultimately, self-actualization is manifested in the character’s capacity for self-acceptance, healing, and rebuilding life with renewed purpose. These findings highlight that literary works can represent the gradual fulfillment of human needs, offering insights into the complexity of psychological growth within narrative contexts.